LEGAL STATUS OF MASS EVENT ORGANIZERS AND ITS DEFINITION - Svystovych, Roman (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the scientific research is to propose and justify the definition of the legal status of organizers of mass events, which is quite important in both social and political life in modern Ukraine. The scientific article analyzes the legal status of mass event organizers, which is not officially defined today. Discussion: mass event organizers are individuals who are mostly not officials, they perform their tasks not on a permanent basis, but when carrying out the specified activity, that is, organizing and holding mass events, they have certain rights and obligations. Since mass events are held quite often in Ukraine, it is necessary to determine the rights and obligations of organizers in the relevant regulatory act. However, after gaining independence, the Verkhovna Rada of Ukraine made several attempts to adopt the law «On Mass Events», but there was not enough political will. Today, mass event organizers have certain rights and obligations and they use them when carrying out actions aimed at holding mass events. To a certain extent, the legal status of mass event organizers can be distinguished in the Constitution of Ukraine, as well as in a number of international legal acts. Results: it is concluded that the separation of the legal status of organizers of mass events is important for the democratization of public life in Ukraine, it is necessary to consider this issue in the Verkhovna Rada of Ukraine. In the scientific aspect, it is proposed to define the legal status of organizers of mass events as a special legal status of the specified persons. In addition, Ukraine lacks relevant legal norms regarding the liability of organizers of mass events for violations of human rights, as well as public order and public safety during mass events. It is proposed to make appropriate amendments to the Criminal Code of Ukraine and the Code of Ukraine on Administrative Offenses in order to regulate these legal relations.